Late sowing date influence on wheat and triticale crop yields as a draught management tool - Kawa A. Ali; Sami Muhammad Amin; Rashid A. Abdullah (Journal of the Saudi Society of Agricultural Sciences, 2021)
Three different wheat and triticale genotypes (two wheats; CYMMIT and Aras, and one triticale Rwaida) were evaluated under five late sowing dates at Einkawa farm of Erbil Dry-land Research Center, KRG –Iraq (Lat 350 0′ 38″ N Long 430 0′ 24″ E) for two growing seasons 2015–2016 and 2016–2017 to test any agronomic variance characteristics as a strategy to reduce risks attributable to inadequate precipitation in order to achieve proper soil plowing humidity. Results pointed to superiority of Rwaida genotype, and earliest Sowing date with their interaction V3D1 in grain yield (193.1, 241.6, and 266 g m−2 respectively) due to higher chlorophyll content in their flag leaves and taller plants that push the flag leaves up to receive higher amounts of irradiance. leading to the conclusion of achieving tillage as soon as possible with the assumption of reducing grain yield to a half when delaying sowing date for more than two months from the advised sowing date in the region (15th Nov.).